Navigating the Gen Z Paradox: A Qualitative Study of Career Aspirations, Digital Individualism, and Work–Life Integration among Generation Z - Iqbal Bafadal; Muhammad Awwad (Psikostudia : Jurnal Psikologi, 2026)
This study explores the psychosocial paradox experienced by Generation Z in Eastern Indonesia by examining the dynamic interaction between their career aspirations, digital individualism, and work–life integration from a guidance and counseling perspective. Employing a qualitative descriptive design rooted in a constructivist epistemological position, the study utilized Braun and Clarke’s framework for reflexive thematic analysis (RTA). Data were generated through semi-structured individual interviews, structured naturalistic observations, and researchers' reflexive journals from participants across West Nusa Tenggara (NTB) and East Nusa Tenggara (NTT). The analysis revealed three prominent themes: (1) Aspiration–Behavior Discordance, characterized by high career ambitions but critically low active preparation or strategic planning; (2) Digital Individualism and Community Disengagement, marked by a strong preference for digitally mediated autonomous interactions and minimal participation in physical communal organizations; and (3) Reconceptualization of Work and Life Integration, where participants prioritize personal flexibility, autonomy, and psychological well-being over traditional, purely financial metrics of professional success. These findings demonstrate that Generation Z's vocational and psychosocial growth operates as an interconnected developmental system navigating digital affordances alongside local socio-economic realities and structural constraints. Consequently, contemporary counseling interventions must move beyond basic occupation-centered guidance to holistically integrate digital well-being, self-regulation, and community connectedness to help youth translate abstract aspirations into adaptive actions.Penelitian ini mengeksplorasi paradoks psikososial yang dialami oleh Generasi Z di Indonesia Timur dengan mengkaji interaksi dinamis antara aspirasi karier, individualisme digital, dan integrasi kehidupan–kerja dari perspektif bimbingan dan konseling. Menggunakan desain deskriptif kualitatif yang berakar pada posisi epistemologi konstruktivis, penelitian ini menerapkan analisis tematik refleksif (RTA) berdasarkan kerangka kerja Braun dan Clarke. Data dikumpulkan melalui wawancara individual semi-terstruktur, observasi naturalistik terstruktur, dan jurnal refleksif peneliti dari para partisipan di wilayah Nusa Tenggara Barat (NTB) dan Nusa Tenggara Timur (NTT). Analisis mengidentifikasi tiga tema utama: (1) Ketidakselarasan Aspirasi–Perilaku), yang ditandai dengan ambisi karier yang tinggi namun disertai dengan sangat rendahnya persiapan nyata atau perencanaan strategis; (2) Individualisme Digital dan Keterputusan Komunitas, yang dicirikan oleh preferensi kuat terhadap interaksi otonom termediasi digital dan minimnya partisipasi dalam organisasi komunal fisik; serta (3) Rekonseptualisasi Integrasi Kerja dan Kehidupan, di mana partisipan memprioritaskan fleksibilitas pribadi, otonomi, dan kesejahteraan psikologis di atas metrik kesuksesan profesional yang murni berbasis finansial tradisional. Temuan ini menunjukkan bahwa pertumbuhan vokasional dan psikososial Generasi Z berjalan sebagai sebuah sistem perkembangan yang saling terhubung dalam menavigasi peluang digital di tengah realitas sosio-ekonomi dan keterbatasan struktural lokal. Oleh karena itu, intervensi konseling kontemporer harus melampaui model bimbingan tradisional yang berorientasi pada jabatan, dengan mengintegrasikan kesejahteraan digital, regulasi diri, dan keterhubungan komunitas secara holistik demi membantu generasi muda mentransformasikan aspirasi abstrak mereka menjadi tindakan nyata yang adaptif.